Laypeople and dental professionals' perception of the aesthetic outcome of two treatments for missing lateral incisors - Cecilia Hedmo; Rune Lindsten; Eva Josefsson (Wiley, 2022)
Abstract Objective To investigate laypeople and dental professionals' opinions of the aesthetic outcome from implant therapy (IT) and orthodontic space closure (SC) for missing maxillary lateral incisors. Material and methods Evaluation was performed by three groups: laypeople 20-30 years of age (n = 26), laypeople 50-70 years of age (n = 26) and orthodontists (n = 25). The assessors viewed photographs of 44 different cases treated with IT or SC, and made an evaluation of the aesthetics. Results The gingival color adjacent to the replaced tooth was rated as having better aesthetics in the SC cases (p = 0.000). The orthodontists preferred the aesthetics of the dentition in the SC cases (p = 0.042). The young laypeople, compared to the older laypeople and orthodontists, were more dissatisfied with the color of the tooth replacing the missing lateral incisor in SC cases (p = 0.043). Conclusion The color of the gingiva adjacent to the implant‐supported crowns had a lower aesthetic rating than the SC group. Laypeople rated both treatments as equally good. The orthodontists had a slight preference for the aesthetics in the SC cases.